GNE myopathy (Nonaka myopathy) - Galina E. Rudenskaya; Alena L. Chukhrova; Oksana P. Ryzhkova (Анналы клинической и экспериментальной неврологии, 2019)
GNE myopathy (Nonaka myopathy) is a rare recessive muscular dystrophy associated with the GNE gene, which is involved in sialic acid synthesis. Typical onset is in the third decade of life with distal weakness of the arms and legs, gradually progressing to the proximal muscles, along with severe generalized myopathy and loss of ambulation usually occurring 1020 years after disease onset. Exomе sequencing methods have greatly increased the possibility of diagnosis of this and other rare hereditary diseases. A case of GNE myopathy with onset at 26 years of age and a prolonged search for a diagnosis, which was finally made after 12 years, is presented. Whole exome sequencing with subsequent Sanger sequencing verification found compound heterozygosity of the GNE mutations not previously described: с.787delA (p.Met263CysfsTer4) and c.2005GT (p.Ala669Ser). Differential diagnosis and a literature review are presented.